24 Anti-microbial envelopes are associated with very low device infection rate for cardiac implantable electronic devices (awaiting final version). (October 2018) - Murphy, M; Galvin, J; Ryan, P; Keelan, E; Mahon, N; O'Neill, J; Keaney, J
Abstract : Background: Device Infection is a recognised complication of cardiac implantable electronic device (CIED) insertion. Reported incidence of CIED infection vary widely, and range from 1.0% for pacemakers to up 9.5% for cardiac resynchronisation defibrillators (CRT-d). The risk of infection is 2–4-fold higher for CIED replacement. CIED infection is associated with significant patient morbidity and mortality rate of up to 27% at 2 years. Recently an antibacterial pouch (Tyrx TM, Medtronic) has been developed. This absorbable pouch elutes rifampicin and minocycline from a monofilament polypropylene mesh. Use of the TYRX pouch has been associated with reduced CIED infection. Real-world data on the efficacy of the envelope remains limited. Methods: We performed an retrospective review of the CIED infection rate for all devices implanted with a Tyrx TM pouch from September 2015 to October 2017 in our institution. Patient or procedural factors known to increase the risk of infection were documented in each case. Results: 63 patients had CIEDs implanted along with a Tyrx TM pouch during the period under review. 14 (22%) were female. The average age at implant was 64 years±13. Five patients had chronic kidney disease (eGFR <30 mls min-1), and 1 had a prior kidney transplant. 20 (32%) of the patients were diabetic. 2 patients were on chronic steroid therapy and 3 were on other immunosuppressants. 20 patients (32%) were on oral anticoagulants. Only 5 cases were de-novo device implants and the remaining 58 were device generator changes, pocket revisions or upgrades. 12 cases involved CRT-ds. 50 were for insertion or replacement of an ICD, 35 of which were dual-chamber devices. The mean length of follow-up was 367±225 days. There were no CIED pocket infections on follow-up. No CIED pocket re-explorations were required. 2 patients received short-courses of antibiotics for suspected suture-site infections. One patient on warfarin received prophylactic antibiotics for a site-hematoma; the patient remained apyrexial with a CRP <1. Conclusion: Our study included many patients with factors associated with increased infection rate. Over a mean follow-up period of >1 year, no patients with a CIED implanted along with a TyrxTM antibacterial pouch had CIED pocket infection. Though the numbers under review were small, our results compare very favourably with previously published rates of CIED infection, and lend further support to the use of antibacterial pouches to reduce the risk of device infection.